The icon & the idealist : Margaret Sanger, Mary Ware Dennett, and the rivalry that brought birth control to America - Gorton, Stephanie, 1984- (Ecco, an imprint of HarperCollinsPublishers, 2024)
"In the 1910s, as the birth control movement was born, two leaders emerged: Margaret Sanger and Mary Ware Dennett. While Sanger would go on to found Planned Parenthood, Dennett's name has largely faded from public knowledge. Each held a radically different vision for what reproductive autonomy and birth control access should look like in America ... Meticulously researched and vividly drawn, [this book] reveals how and why these two women came to activism, the origins of the clash between them, and the ways in which their missteps and breakthroughs have reverberated across American society for generations"--